2022
DOI: 10.3390/joitmc8030144
|View full text |Cite
|
Sign up to set email alerts
|

Building a Bridge: Knowledge Sharing Flows into Entrepreneurial Ecosystems

Abstract: Entrepreneurial ecosystems remain under-theorised and conceptually fragmented, making it challenging to comprehend their disposition and performance in the business process. Accordingly, in this research, we explored how knowledge sharing flows through entrepreneurial ecosystems to make analyses and trials to assess new ventures’ creation, continuity, and development opportunities. We carried out a systematic literature review on the Web of Science database. The analysis was carried out in two stages: (i) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 124 publications
0
14
0
2
Order By: Relevance
“…Our findings revealed that a significant portion of knowledge sharing in startups occurs informally, driven by a sense of collectivism, trust, and recognition among individuals and organisations [99]. The critical outcomes reported were enhanced networking opportunities through incubation and acceleration programs, facilitating expanding connections [100]. Access to technical knowledge, capital, partnership market contacts, and customer acquisition was commonly mentioned [14,24,101].…”
Section: Theoretical and Practical Contributions And Implicationsmentioning
confidence: 95%
“…Our findings revealed that a significant portion of knowledge sharing in startups occurs informally, driven by a sense of collectivism, trust, and recognition among individuals and organisations [99]. The critical outcomes reported were enhanced networking opportunities through incubation and acceleration programs, facilitating expanding connections [100]. Access to technical knowledge, capital, partnership market contacts, and customer acquisition was commonly mentioned [14,24,101].…”
Section: Theoretical and Practical Contributions And Implicationsmentioning
confidence: 95%
“…Knowledge sharing is considered one of the leading research topics in management and can be defined as interactions between individuals that provide an exchange of experiences, skills and tacit and explicit knowledge ((R. Andrade et al, 2022) Serenko & Bontis, 2016Helmstadter, 2003;Hogel et al, 2003). Cummings (2003) understands knowledge sharing as how organisations access their knowledge and that of other organisations, while Gibbert and Krause (2002) understand it as the collaborator's desire to give others the knowledge acquired or created by yes.…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…Contrary to the theoretical work of [9], which conceptualizes and theoretically reviews entrepreneurship to propose research themes on this topic, our analysis is a bibliometric review that is novel concerning the issue analyzed, as it originally relates to a mapping analysis of PPC as a practical instrument for digital entrepreneurs to strengthen their firms. Added to this fact, other bibliometric literature published using SCOPUS data on VOSviewer relates to other socioeconomic topics and issues linked to entrepreneurship, such as privacy [32], digital technologies and circular economy [33], rural mother's empowerment [34], intrapreneurship [35], strategic entrepreneurship [36], immigrant entrepreneurship [37], knowledge sharing and entrepreneurial ecosystems [38], and female entrepreneurship [39].…”
Section: Literature Reviewmentioning
confidence: 99%